2022
DOI: 10.7717/peerj.13122
|View full text |Cite
|
Sign up to set email alerts
|

AreToxoplasma-infected subjects more attractive, symmetrical, or healthier than non-infected ones? Evidence from subjective and objective measurements

Abstract: Background Parasites are among the main factors that negatively impact the health and reproductive success of organisms. However, if parasites diminish a host’s health and attractiveness to such an extent that finding a mate becomes almost impossible, the parasite would decrease its odds of reproducing and passing to the next generation. There is evidence that Toxoplasma gondii (T. gondii) manipulates phenotypic characteristics of its intermediate hosts to increase its spread. However, whether T. gondii manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…On the other hand, recent evidence revealed that T . gondii infection augments sexual behavior and attractiveness in humans [ 61 ] and experimentally infected rodents [ 5 ]. In this regard, Borráz-León et al [ 61 ] assessed several factors related to attractiveness among T .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, recent evidence revealed that T . gondii infection augments sexual behavior and attractiveness in humans [ 61 ] and experimentally infected rodents [ 5 ]. In this regard, Borráz-León et al [ 61 ] assessed several factors related to attractiveness among T .…”
Section: Discussionmentioning
confidence: 99%
“…They also assessed the attractiveness and perceived health of facial pictures of T . gondii -infected and non-infected subjects by an independent group of raters and found that both infected women and men were rated as more attractive and healthier than non-infected individuals [ 61 ]. Increased testosterone could enhance sexual behavior and attractiveness in infected subjects and could increase mating opportunity and transmission of T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, infections make patients sexually more attractive. Since they have more sexual partners, their reproductive success may increase (Borráz-León et al 2022)…”
Section: Discussion Interpretation and Biological Examplesmentioning
confidence: 99%
“…– of reducing its longevity (Yule et al ., 2013 ). Toxoplasma gondii , a widespread infection in rodents and humans, increase predation pressure (Berdoy et al ., 1995 ) and traffic accidents (Gohardehi et al ., 2018 ) of infected hosts while, on the other hand, makes them sexually more attractive potentially increasing their reproductive success (Dass et al ., 2011 ; Borráz-León et al ., 2022 ). We cannot quantify the combined fitness effects of reduced lifespan and (presumably) increased reproductive success of infected hosts; however, host adaptations to combat Toxoplasma infections indicate that it is unfavourable at the lineage level.…”
Section: Infection-induced Harms Across 4 Levels Of Hierarchical Orga...mentioning
confidence: 99%